Interactive Effects of Ambient Temperature and Light Sources at High Relative Humidity on Growth Performance and Blood Physiological Variables in Broilers Grown to 42 Day of Age - Olanrewaju , Hammed A.; Purswell, Joseph L.; Collier, Stephanie D.; Branton, Scott L. (International Journal of Poultry Science, 2016)
Objective: The objective of the study is to evaluate the interactive effects of ambient temperature and light sources at high relative humidity on growth performance and blood physiological reactions in broilers grown to 42 days of age. Methodology: The experiment consisted of two levels (Moderate = 21.1°C and high = 26.7°C) of temperatures and two light sources (ICD and PSF-LED) at high relative humidity (80%). A total of 532 1 day-old Ross 708 chicks were randomly distributed into 8 environmentally-controlled rooms (22 males and 22 females chicks per room). Feed and water were provided ad libitum. Light treatment started from 1 day, while temperature and RH were applied continuously from 22 days through 42 days. Both feed intake and bird’s weight were recorded on 1 and 21day (before initiation of the treatments), 28 and 42 day for the growth performance. Also, wing brachial vein blood (3 mL) samples were collected on weigh days from six (3 males/3 females) randomly selected chicks from each room. Results: Treatments with only high ambient temperature significantly (p